Implementation of Sensor-Based Automatic Trash Can Technology to Improve Waste Sorting Awareness at Nusaputera National School in Semarang - Andre Kurniawan Pamudji; T. Brenda Chandrawati; Gita Claudia; Stephani Inggrit Swastini Dewi (Faculty of Smart Technology and Engineering, Universitas Kristen Maranatha, Bandung, Indonesia, 2025)
Good waste management is one of the current global challenges. Schools are one of the places to form environmental awareness among students. Nusaputera National School in Semarang, as a partner in this community service program, faces problems related to the lack of education on good waste sorting and limited infrastructure that supports these activities. To overcome this problem, this community service program implements automatic sensor-based trash can technology that facilitates the waste disposal process so that students' awareness of waste management can increase. Through information dissemination and education involving students and teachers from various levels of education, this program has succeeded in increasing understanding of proper waste sorting. Evaluations conducted during the implementation of the program showed that the automatic trash can technology succeeded in attracting students' interest and increasing their awareness of the importance of waste management. The sustainability of this program is planned by providing further training for teachers and students and introducing the same technology to other schools in the Semarang area. The results of this program are expected to have a wider impact in creating a culture of sustainable waste sorting in the educational environment, while supporting Nusaputera National School's vision in realizing technology-based and environmentally friendly education.